We all need to know about HIV cure research: a case report - Olubanke Davies; Julie Fox (Elsevier, 2015)
A cure for HIV is not near, yet publicity surrounding the possibility of cure is high. We present the case of an individual with acute HIV who delayed antiretroviral therapy due to misinformed expectations of availability of cure treatments. Researchers and the media need to be mindful of prematurely raising hope of a cure.